2008
DOI: 10.1007/s11738-007-0132-4
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine affects adventitious rooting and causes biochemical changes in the hypocotyl cuttings of mung bean (Phaseolus aureus Roxb.)

Abstract: Caffeine (1,3,7-trimethylxanthine), a purine alkaloid found naturally in over 100 plant species, has recently been viewed as a safe chemical for management of pests including molluscs, slugs, snails, bacteria, and as a bird deterrent. It possesses phytotoxicity against plant species, yet the mechanism of action is lacking. A study was conducted to determine the effect of caffeine on the rooting of hypocotyl cuttings of mung bean (Phaseolus aureus) and the associated biochemical changes. At lower concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…Similar pattern was shown in research on Oryza sativa L. by Smyth [24] who reported 2.5 mM caffeine suppression of shoot elongation by 50% and root elongation by 90%. Also in mung bean (Phaseolus aureus), Batish et al [25] reported that caffeine reduced root number and length produced by hypocotyl cuttings.…”
Section: Effect Of Caffeine Treatment On In Vitro-grown and Soil-growmentioning
confidence: 99%
“…Similar pattern was shown in research on Oryza sativa L. by Smyth [24] who reported 2.5 mM caffeine suppression of shoot elongation by 50% and root elongation by 90%. Also in mung bean (Phaseolus aureus), Batish et al [25] reported that caffeine reduced root number and length produced by hypocotyl cuttings.…”
Section: Effect Of Caffeine Treatment On In Vitro-grown and Soil-growmentioning
confidence: 99%
“…Thus, apart from detoxification of coffee pulp by F. solani, the process could also be used for the production of a value added product like theophylline. Process parameters namely pH (3)(4)(5)(6)(7)(8)(9), temperature (20-40°C) and inoculum size (1-7 × 10 5 spores/ml) were optimized for biodecaffeination by F.solani using RSM. Three responses namely caffeine degradation (Y 1, Y 3, Y 5 ), theophylline formation (Y 2, Y 4, Y 6 ) and 3 methyl xanthine formation (Y 7 ) were evaluated by RSM ( Table 3).…”
Section: Metabolite Profiling Of Biodecaffeinationmentioning
confidence: 99%
“…Disposal of effluents containing caffeine into lakes could cause drinking water to become non-potable [4]. Moreover, the disposal of caffeine wastes into soil could cause infertility by inhibiting seed germination and growth of seedlings [5,6]. These wastes are often released into water bodies or dumped near production sites, causing severe environmental hazard [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Ellipticine as an important plant second metabolite is a kind of topoisomerase II inhibitor, which can mediate the damage process of DNA, and participate in the oxidative phosphorylation uncoupling of mitochondria. Batish et al (2008) pointed out that ellipticine could suppress the rooting process of Phaseolus aureus. IAA is an important plant hormone, which is involved in the growth and differentiation process.…”
Section: Part Iii: the Difference Of Substance Composition In The Actmentioning
confidence: 99%